Wear Resistance Property of Hardfacing Weld Overlays Containing Metal Carbides - Masahito Ban (Japanese Society of Tribologists, 2012)
High-chromium white iron based weld overlay materials containing metal carbides were deposited, and the wear performances were evaluated using a dry sand/rubber wheel test according to American Society for Testing and Materials G65-04 standard. The test results demonstrated that the weld overlay materials showed relatively smaller mass losses, and had superior property of wear-resistance compared to conventional high-chromium white cast irons. The results of X-ray diffraction analysis, and optical and scanning electron microscopy observations revealed that the microstructures of the weld overlays were featured by the finer and harder carbides densely dispersed in the Fe-Cr-C system matrix compared with the high-chromium white cast irons. It was implied that the wear resistance was enhanced with an increase in the coverage rate of carbides to the matrix, and more densely dispersion of the finer and harder carbides provided mechanical support to depress the wear against asperities of the abrasion. Therefore, the weld overlays with densely dispersed finer and harder carbides in the matrix exhibited higher wear resistance.